The divergent adolescent and adult transitions of Latin American undocumented minors. (4th January 2023) - Diaz‐Strong, Daysi Ximena; Gonzales, Roberto G.
Abstract: Undocumented immigrants arriving in the United States as minors navigate tremendous constraints as they transition into adolescence and adulthood. Exclusionary immigration laws profoundly shape and complicate the attainment of important milestones and the decisions undocumented minors make about their adult futures. A significant body of research, largely focused on children who arrive when they are 12 years old and younger, has examined the impact of legal exclusion on the coming‐of‐age experiences of undocumented minors. However, we know less about the experiences of teenage arrivals. In this article, we focus on young Latin American migrants and provide an overview of how legal exclusion contours undocumented minors' adolescent and adult transitions; we also call attention to the divergent experiences of youth who arrive during childhood and youth who arrive during adolescence. Throughout the article, we emphasize how the timing of immigration—the developmental stage when a young person migrates—creates meaningful differences in the barriers undocumented minors confront.